1990
DOI: 10.1148/radiology.177.2.2217795
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic portal venous system: variations demonstrated with duplex and color Doppler US.

Abstract: Seventeen cases of variations of the intrahepatic portal venous system were investigated with use of duplex and color Doppler ultrasound (US). Seven cases involved absence of the horizontal segment of the left portal vein, with portal supply to the left lobe arising from the right lobe. The 10 remaining cases involved variations of intrahepatic portal branching resulting from absence of the right portal vein, taking four patterns. It is thought that these findings represent variants of normal. These variants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 0 publications
1
36
0
1
Order By: Relevance
“…This study and other case reports demonstrate the importance of long-term follow-up of infants with PVT. 2,19 Atrophy of the left hepatic lobe, previously considered a normal variant, 20,21 was diagnosed in 30 infants. A correlation between hepatic lobar atrophy and ipsilateral portal vein obstruction has been reported in adults.…”
Section: Discussionmentioning
confidence: 99%
“…This study and other case reports demonstrate the importance of long-term follow-up of infants with PVT. 2,19 Atrophy of the left hepatic lobe, previously considered a normal variant, 20,21 was diagnosed in 30 infants. A correlation between hepatic lobar atrophy and ipsilateral portal vein obstruction has been reported in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of bifurcation of the portal vein is a rare anomaly and a large-scale study performed by ultrasound examination reported that its incidence was only 0.09% [1]. The complicated development of the portal vein occurs early in fetal life.…”
mentioning
confidence: 99%
“…Knowledge of these typical fi ndings should help Keywords liver · portal vein · anatomy · ultrasound · doppler Although abdominal ultrasound (US) examinations are routinely carried out in the clinical setting throughout Japan, and although congenital anomaly of the portal vein is not remarkably infrequent, few US fi ndings have been reported. [1][2][3][4] We describe a case of congenital absence of the horizontal (transverse) portion of the left portal vein. Knowledge of such ultrasound fi ndings can help prevent hazardous misdiagnoses.…”
Section: Discussionmentioning
confidence: 99%